FAKTOR Ã¢â¬â FAKTOR YANG MEMPENGARUHI KETUNTASAN BELAJAR AKUNTANSI : MOTIVASI BELAJAR SEBAGAI VARIABEL INTERVENING - Khafid, Muhammad (Universitas Negeri Semarang, 2008)
The purpose of this research is to find out the influence of family environment,school environment, teaching method and learning motivation towards the masterylearning of accounting students. The population taken in this research is students ofgrade XI MA YASPIA Grobogan as many as 116 students, that are divided into twoclasses; XI A and XI B. The sample taken is students of grade XI MA YASPIAGrobogan who are 100 students in total. The variable being addressed is variableexogen which covers family envoronment, school environment and teaching method.Meanwhile, learning motivation as the intervening variable and endogen variable aremastery learning of accounting. The method of data gathering is documentation andquesionaire. The method of data analysis is Structural Equation Modelling (SEM).The result of the reserarch showed that family environment, school environment,teaching method and learning motivation influenced the studentsÃ¢â¬â¢ accounting mastery.Fisrt, the family environment influenced the studentsÃ¢â¬â¢ accounting mastery directly,(13%), with CR = 1.96 and a p value of 0.049 lower than 0.05. Second, the learningmotivation influenced the studentsÃ¢â¬â¢accounting mastery, (8.91%), with CR = 3.085 anda p value of 0.002 lower than 0.05. Third, the school environment influenced thestudentsÃ¢â¬â¢ accounting mastery directly (27%), with CR = 0.028 and a p value 0.000lower than 0.05 and it had indirect influence base on motivation point of view(11.55%) with CR = 4.111 and a p value of 0.000 lower than 0.05. Finally, the methodused in teaching influenced the studentsÃ¢â¬â¢ accounting mastery (34%) with CR = 5.171and a p value of 0.000 lower than 0.05 and base on motivation point of view, it hadinderect influence (7.26%) with CR = 2.597 and a p value of 0.009 lower than 0.05.Kata Kunci: lingkungan keluarga, lingkungan sekolah, metode pembelajaran, motivasibelajar, ketuntasan belajar.